Augmentation of Glucose Transport in Macrophages After Particle Ingestion - Bonventre, Peter F. (1974)
Guinea pig and mouse peritoneal macrophages in culture transport glucose by a specific, saturable system with characteristics compatible with facilitated diffusion. Phagocytosis of killed staphylococci or polystyrene latex spheres results in a significant increase in uptake of 2-deoxy-d-glucose. Reciprocal plot analysis showed that the K(m) values were lowered as a consequence of phagocytosis by a factor of between 2 and 3 in both cell types; V(max) values were not significantly changed. The nature of the intracellular sugar pool was analyzed and found to consist of free and phosphorylated 2-deoxy-d-glucose at a relatively constant ratio of 1:2 after periods of uptake between 1 and 20 min. Phagocytosis resulted in increased levels of both free and phosphorylated sugars in the cytoplasm. Since the K(m) values were lowered, augmented glucose uptake could not be accounted for by altered hexokinase activity. It was concluded that phagocytosis induces changes in the glucose transport system per se. The data are compatible with the metabolic changes known to be associated with particle ingestion by phagocytic cells. The mechanism by which glucose transport is augmented after loss of significant amounts of cell surface during the phagocytic process is not yet known.